MICROMOLAR INTRACELLULAR HYDROGEN PEROXIDE DISRUPTS METABOLISM BY DAMAGING IRON-SULFUR ENZYMES - Jang, Soojin (J Biol Chem, 2006)
An Escherichia coli strain that cannot scavenge hydrogen peroxide has been used to identify the cell processes that are most sensitive to this oxidant. Low micromolar concentrations of H(2)O(2) completely blocked the biosynthesis of leucine. The defect was tracked to the inactivation of isopropylmalate isomerase. This enzyme belongs to a family of [4Fe-4S] dehydratases that are notoriously sensitive to univalent oxidation, and experiments confirmed that other members were also inactivated. In vitro and in vivo analyses showed that H(2)O(2) directly oxidizes their solvent-exposed clusters in a Fenton-like reaction. The oxidized cluster then degrades to a catalytically inactive [3Fe-4S] form. Experiments indicate that H(2)O(2) accepts two consecutive electrons during the oxidation event; as a consequence, hydroxyl radicals are not released, the polypeptide undamaged, and the enzyme is competent for reactivation by repair processes. Strikingly, in scavenger-deficient mutants the H(2)O(2) that was generated as an adventitious by-product of metabolism (< 1 μM) was sufficient to damage these [4Fe-4S] enzymes. This result demonstrates that aerobic organisms must synthesize H(2)O(2) scavengers to avoid poisoning their own pathways. The extreme vulnerability of these enzymes may explain why many organisms, including mammals, deploy H(2)O(2) to suppress microbial growth.